(untitled) (Research, Society and Development, 2020)
This study analyzed the knowledge of medical and law students about the restrictive measures adopted during the COVID-19 pandemic and the implications in the fundamental rights of the individuals. A google forms questionnaire was prepared and sent by WhatsApp to medical students and law students. The survey included questions about social isolation and if it violates or not the citizens’ and humans’ rights. Descriptive statistics were performed, and comparisons between medical and law students were made with chi-square and independent t-tests. A higher percentage of medical students were taken precautionary measures than law students. Internet and TV are the most used to stay up to date. Most medical and law students believed that the restrictive measure of social isolation violates the rights guaranteed to citizens. However, the majority of them believed that the citizens’ rights to life and health should prevail over the citizens’ right to come and go.